2017
DOI: 10.1007/978-1-4939-7234-0_13
|View full text |Cite
|
Sign up to set email alerts
|

The N-butyl-N-4-hydroxybutyl Nitrosamine Mouse Urinary Bladder Cancer Model

Abstract: Urinary bladder cancer (UBC) is a common and complex malignancy, with a multifactorial etiology, like environmental factors, such as cigarette smoking, occupational exposure, and genetic factors.UBC exhibits considerable genotypic and phenotypic heterogeneity. Among all UBC lesions, urothelial carcinoma is the most frequently observed histological type. Despite all the developments made in urologic oncology field, therapeutic options remain inadequate. There is urgency for the identification and development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…The most established mechanism involves the formation of endogenous nitrosamines from nitrites that are particularly abundant in processed meats (17). Experimental studies have confirmed that some nitrosamine metabolites induced bladder tumors in animal models (18). In addition, tobacco smoke, a well-established risk factor for bladder cancer, is a main source of exogenous exposure to nitrosamines.…”
Section: Discussionmentioning
confidence: 99%
“…The most established mechanism involves the formation of endogenous nitrosamines from nitrites that are particularly abundant in processed meats (17). Experimental studies have confirmed that some nitrosamine metabolites induced bladder tumors in animal models (18). In addition, tobacco smoke, a well-established risk factor for bladder cancer, is a main source of exogenous exposure to nitrosamines.…”
Section: Discussionmentioning
confidence: 99%
“…To test our hypothesis that mice with bladder cancer would harbor a distinct urinary "oncobiome", we used an established model in which a dilute bladder-specific carcinogen (n-butyl-n-(4-hydroxybutyl) nitrosamine, BBN) is administered to mice in their drinking water. The BBN model, a widely used and well-established model of bladder carcinogenesis, [22,23] reliably leads to tumor formation in both mice and rats. Although the incidence of cancer is not 100%, this can be seen as an advantage given that an array of pathologies are obtained.…”
mentioning
confidence: 99%
“…Bladder, as an organ of the urinary system in the body, is a necessary path for urine excretion. When bladder lesions occur, such as nearby ureteral obstruction, internal cancer and other conditions that make the urinary system unable to work properly, the construction of the model is indispensable (Obajemu et al, 2018, Xiao et al, 2017, Sole et al, 2019, Oliveira et al, 2018). In urinary clinical diagnosis, patients are often required to insert the catheter for catheterization, so modeling is one of the methods to accelerate the understanding of its principle.…”
Section: Discussionmentioning
confidence: 99%